Phylogenetic relationships and regional spread of meningococcal strains in the meningitis belt, 2011–2016 - Topaz, Nadav (EBioMedicine, 2019)
BACKGROUND: Historically, the major cause of meningococcal epidemics in the meningitis belt of sub-Saharan Africa has been Neisseria meningitidis serogroup A (NmA), but the incidence has been substantially reduced since the introduction of a serogroup A conjugate vaccine starting in 2010. We performed whole-genome sequencing on isolates collected post-2010 to assess their phylogenetic relationships and inter-country transmission. METHODS: A total of 716 invasive meningococcal isolates collected between 2011 and 2016 from 11 meningitis belt countries were whole-genome sequenced for molecular characterization by the three WHO Collaborating Centers for Meningitis. FINDINGS: We identified three previously-reported clonal complexes (CC): CC11 (n = 434), CC181 (n = 62) and CC5 (n = 90) primarily associated with NmW, NmX, and NmA, respectively, and an emerging CC10217 (n = 126) associated with NmC. CC11 expanded throughout the meningitis belt independent of the 2000 Hajj outbreak strain, with isolates from Central African countries forming a distinct sub-lineage within this expansion. Two major sub-lineages were identified for CC181 isolates, one mainly expanding in West African countries and the other found in Chad. CC10217 isolates from the large outbreaks in Nigeria and Niger were more closely related than those from the few cases in Mali and Burkina Faso. INTERPRETATIONS: Whole-genome based phylogenies revealed geographically distinct strain circulation as well as inter-country transmission events. Our results stress the importance of continued meningococcal molecular surveillance in the region, as well as the development of an affordable vaccine targeting these strains. FUND: Meningitis Research Foundation; CDC's Office of Advanced Molecular Detection; GAVI, the Vaccine Alliance.